An interpretation of the life of Viscount Shibusawa - Obata, Kyugoro (Tokyo insatsu kabushiki kaisha, 1937)
Through this volume the Viscount will long live on the stage of international drama. His merits and contributions will be handed down from generation to generation in a world-wide fashion, thus stimulating and elevating humanity to a higher level.